Extremal Problems of Approximation Theory in Linear Spaces - Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We propose an approach that enables one to pose and completely solve main extremal problems in approximation theory in abstract linear spaces. This approach coincides with the traditional one in the case of approximation of sets of functions defined and square integrable with respect to a given σ-additive measure on manifolds in R m, m ≥ 1.